Approaches of dentomaxillofacial and medical radiologists about reporting - Ozlem Üçok; Aylin Kayadüğün; İlkay Peker (Cumhuriyet University, 2018)
Objectives: Radiological reporting is a relatively new and challenging issue in dentomaxillofacial radiology, whereas it has been performed so many years in medical radiology. The purpose of this study is to compare approaches of dentomaxillofacial and medical radiologists regarding radiology reporting.  Materials and Methods: Dentomaxillofacial and medical radiologists were invited by e-mail. The participants filled a survey regarding the features of their own radiology reports. The study was based on two independent groups (dentomaxillofacial and medical radiologists). Mann-Whitney U test was used for two independent groups. Results: 285 radiologists in total (115 dentomaxillofacial and 170 medical radiologists) participated in this survey. Structured radiologic reports were mostly preferred by both dentomaxillofacial (53.9%) and medical radiologists (77%), but statistically significant difference was found between two groups (p<0.05). Although dentomaxillofacial (79.1%) and medical (81.2%) radiologists mostly reported that their own reports consisted of separate headings as clinical information, findings and conclusion, there was a statistically significant difference between two groups (p<0.05). The majority of dentomaxillofacial (99.1%) and medical (99.4%) radiologists agreed regarding radiology training programs should include radiology report construction. Conclusion: This is the first study pointing out the approaches of dentomaxillofacial radiologists about reporting. Good radiological reporting is a relatively new task for dentomaxillofacial radiologists compared to medical radiologists. This study showed that the approaches of dentomaxillofacial and medical radiologists were similar regarding radiological reports.